Cellular circadian period and its deviation associate with Alzheimer’s pathology and brain aging in cognitively impaired older adults - Hyun Woong Roh; Sang Won Seo; Seong Hye Choi; Eun-Joo Kim; Soo Hyun Cho; Byeong C. Kim; Jin Wook Choi; Young-Sil An; Na-Rae Kim; Bumhee Park; Sun Min Lee; So Young Moon; et al. (Proceedings of the National Academy of Sciences, 2026)
Circadian rhythm disruption is recognized as a feature of aging and neurodegenerative disease, yet whether intrinsic cellular circadian properties relate to underlying processes in humans remains unknown. We measured intrinsic circadian period and its deviation from 24 h (Δ-period) using ex vivo bioluminescence in dermal fibroblasts from 135 older adults with cognitive complaints. Associations with plasma biomarkers (pTau-217, neurofilament light chain [NfL], and glial fibrillary acidic protein [GFAP]), amyloid positron emission tomography (PET), structural MRI, cognitive function, and clinical progression were examined within the amyloid–tau–neurodegeneration [ATN (IV)] framework, using multivariable models and Cox regression analyses. The median cellular circadian period was 24.2 h, while Δ-period increased with age. A longer intrinsic circadian period was selectively associated with higher pTau-217, NfL, and GFAP levels and medial temporal atrophy, consistent with Alzheimer’s disease (AD)-related tau pathology, neurodegeneration, and glial activation. In contrast, greater Δ-period was associated with older age, poorer cognitive performance across multiple domains, and more widespread brain atrophy, consistent with broader aging-related neurodegenerative processes. Both longer period (HR = 4.41, 95% CI: 1.52 to 12.83) and greater Δ-period (HR = 2.65, 95% CI: 1.03 to 6.86) independently predicted faster clinical decline. Thus, cellular circadian period and Δ-period capture distinct biological processes—AD-related tau pathology vs. broader aging-related neurodegeneration—and together represent complementary cellular biomarkers with potential prognostic value in older adults with cognitive concerns.